2019
DOI: 10.3390/s19030469
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical DNA Sensors with Layered Polyaniline—DNA Coating for Detection of Specific DNA Interactions

Abstract: A DNA sensor has been proposed on the platform of glassy carbon electrode modified with native DNA implemented between two electropolymerized layers of polyaniline. The surface layer was assembled by consecutive stages of potentiodynamic electrolysis, DNA drop casting, and second electrolysis, which was required for capsulation of the DNA molecules and prevented their leaching into the solution. Surface layer assembling was controlled by cyclic voltammetry, electrochemical impedance spectroscopy, atomic force,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 50 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…The variation of the charge transfer resistance averaged for six individual DNA sensors did not exceed 6%. This coincides well with the results obtained earlier for the polyaniline based DNA sensors with impedimetric and voltammetric signals [3,49].…”
Section: Determination Of Doxorubicin With Dna Sensor Based On Copolysupporting
confidence: 92%
“…The variation of the charge transfer resistance averaged for six individual DNA sensors did not exceed 6%. This coincides well with the results obtained earlier for the polyaniline based DNA sensors with impedimetric and voltammetric signals [3,49].…”
Section: Determination Of Doxorubicin With Dna Sensor Based On Copolysupporting
confidence: 92%
“…To protect the native structure of the aptamer it was proposed to cover the aptamer with additional PANI layer obtained in the same conditions as underlying polymer support. A similar approach showed high efficiency for determination of specific interactions between the native DNA and anthracycline drug . The number of potential cycling chosen corresponded to minimal value providing formation of a continuous film.…”
Section: Resultsmentioning
confidence: 99%
“…Voltammetric measurements were performed in direct current mode using AUTOLAB PGSTAT 302 N (Metrohm Autolab b.v., The Netherlands) at 23±2 °C in 5 mL working cell. Working electrode was home‐made GCE produced accordingly to . Double‐junction Ag/AgCl electrode (CH Instruments, code CHI111) was used as reference electrode and Pt wire as counter electrode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After approval for medical application in 1974, it was criticized for rather high cardiotoxicity and a narrow gap between therapeutic and toxic dozen [47]. Recently we have shown that introduction of DNA in the redox active polymers can be used for sensitive determination of intercalating drugs by their influence on the redox activity of carrier [48]. Polyaniline electropolymerized in the presence of DNA changed its redox activity after treatment with doxorubicin.…”
Section: Resultsmentioning
confidence: 99%